IMPLEMENTASI KEBIJAKAN PENDATAAN PEMILIH DALAM PEMILIHAN ANGGOTA LEGISLATIF PERIODE 2014-2019 (Suatu Studi Di Kabupaten Kepulauan Sula Provinsi Maluku Utara) - Umasangadji, Faruk; Rumapea, Patar; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Members of the legislature or in the context of Indonesia called the House ofRepresentatives (DPR, Provincial DPRD and Regency / City) chosen by the people who have the right tovote or voting on legislation in force. Sula Islands North Maluku Province in the successful legislativeelections is determined by the accuracy factor voters list (DPT) as the final step of the process of voter datacollection policy.Voter Data Collection Policy Implementation in the Legislative Elections with backrest data analysistechniques using qualitative approach requires multiple dimensions such critical role of communication,resources, and the disposition or attitude in the implementation of voter data collection.Based on the research results Documenting voters in Election legislators generally been undone byeffectively but in the dimension of resources and the disposition or attitude is not optimal implementationso that there is also a limiting factor or constraint in the implementation of voter data collection.Keywords: Implementation of policies, collection of voters, legislators